Hajj and Umrah Savings Financing: Study of Financing Model at PT Hannan Nusantara in the Perspective of Maqashid Sharia - Imam Mawardi; Arivatu Ni'mati Rahmatika (Transpublika Publisher, 2024)
Indonesian people have a very high desire to perform worship and use Hajj and Umrah savings financing through a travel company, namely PT Hannan Nusantara. The goal of this paper is to examine the phenomenon of Hajj and Umrah financing, focusing on its alignment with maqashid sharia (the objectives of Islamic law) and maslahah mursalah (public benefit). This study uses a qualitative research method, namely research that produces findings without using statistical calculation procedures in analysis, in conducting qualitative research with a case study approach. The results of this study are There is no guarantee for participants so that financing problems that occur will harm one party, both the Institution and the participants. There is no responsibility for participants after death, because in the principles of Islamic economics, the heirs of the Hajj and Umrah pilgrims are responsible, then there is a misuse of PMA regulation number 8 of 2018 which should have taken the loan funds from A. Partners or Financial Institutions, but in this case PT Hannan Nusantara acquired the Hajj Savings Institution, ownership of PT Hannan Nusantara.